Managerial Behavior and Cost/Profit Efficiency in the Banking Sectors of Central and Eastern European Countries - Stefania P.S. Rossi; Markus Schwaiger; Gerhard Winkler (Oesterreichische Nationalbank (OeNB), 2005)
This paper analyzes cost and profit efficiency level and the managerial behavior of banks in nine Central and Eastern European countries (the Czech Republic, Estonia, Hungary, Latvia, Lithuania Poland, Romania, Slovakia and Slovenia), providing cross-country and time series evidence on the period 1995-2002. A stochastic frontier analysis based on a Fourier flexible form indicates a generally low level of cost efficiency and an even lower level of profit efficiency. However, we also find significant differences among countries and some evidence of an increasing tendency over time in profit efficiency and, to an even stronger extent, in cost efficiency. Cost and profit efficiency scores are negatively correlated both on a country wide as well as on a bank by bank basis. Furthermore, instead of just looking at the determinants of cost and profit efficiency (e.g. asset quality, problem loans and risk), we test several hypotheses of managerial behavior using the Granger causality approach based on the intertemporal relation between bank efficiency, capitalization and problem loans, as proposed by Berger and DeYoung (1997). Even though a static analysis shows a negative correlation between problem loan and efficiency, we find no evidence of bad management hypothesis. Results provide evidence for the bad luck hypothesis suggesting the exogeneity of bad loans triggering inefficiency.
Keywords: G21; G28; C14; D21; 330; Cost and profit efficiency; CEECs; Stochastic frontier analysis; Managerial behavior